Investigation on Slope Stability using Monte Carlo Simulation: A Case Study of Ulu Jelai Hydroelectric Project Slope Parameters & Design Concept - Rahman N.U.A. (Elsevier Ltd, 2023)
In the slope stability, factor of safety still remain the "rule of thumb" in determining how close is the slopes from failure. It is common such limit-equilibrium methods are applied in stability evaluation. Recently, the industry and academics have applied the Finite Element Method (FEM) which are very powerful but require complex understanding of the stability evaluation. The Monte Carlo Simulation (MCS) technique enables the designer or engineer to model the stability evaluation by considering multiple inputs of each parameters/chosen parameters. However, despite its many benefit, it have not widely adopted in the geotechnical world and slope stability evaluation. This could be probably due to the limited experience of engineers with the tool of MCS, and limited published information on the quality/accuracy of the results. To help change the situation, this paper will compare the FOS of the most widely used limit equilibirium methods on various slope cases. In this paper the evaluation of slope stability have been made and the study of Monte Carlo Simulation and the statistics theories is also explained. Excel and RiskAmp software are used for analysis for the probabilistic solution and being compared with the deterministic solution. 2019 Elsevier Ltd.